Modeling Human Retinal Development with Patient-Specific Induced Pluripotent Stem Cells Reveals Multiple Roles for Visual System Homeobox 2. (23rd May 2014) - Phillips, M. Joseph; Perez, Enio T.; Martin, Jessica M.; Reshel, Samantha T.; Wallace, Kyle A.; Capowski, Elizabeth E.; Singh, Ruchira; Wright, Lynda S.; Clark, Eric M.; Barney, Patrick M.; Stewart, Ron; Dickerson, Sarah J.; et al.
Abstract : Human induced pluripotent stem cells (hiPSCs) have been shown to differentiate along the retinal lineage in a manner that mimics normal mammalian development. Under certain culture conditions, hiPSCs form optic vesicle-like structures (OVs), which contain proliferating progenitors capable of yielding all neural retina (NR) cell types over time. Such observations imply conserved roles for regulators of retinogenesis in hiPSC-derived cultures and the developing embryo. However, whether and to what extent this assumption holds true has remained largely uninvestigated. We examined the role of a key NR transcription factor, visual system homeobox 2 (VSX2), using hiPSCs derived from a patient with microphthalmia caused by an R200Q mutation in the VSX2 homeodomain region. No differences were noted between (R200Q)VSX2 and sibling control hiPSCs prior to OV generation. Thereafter, (R200Q)VSX2 hiPSC-OVs displayed a significant growth deficit compared to control hiPSC-OVs, as well as increased production of retinal pigmented epithelium at the expense of NR cell derivatives. Furthermore, (R200Q)VSX2 hiPSC-OVs failed to produce bipolar cells, a distinctive feature previously observed in Vsx2 mutant mice. (R200Q)VSX2 hiPSC-OVs also demonstrated delayed photoreceptor maturation, which could be overcome via exogenous expression of wild-type VSX2 at early stages of retinal differentiation. Finally, RNAseq analysis on isolated hiPSC-OVs implicated key transcription factors and extracellular signaling pathways as potential downstream effectors of VSX2-mediated gene regulation. Our results establish hiPSC-OVs as versatile model systems to study retinal development at stages not previously accessible in humans and support the bona fide nature of hiPSC-OV-derived retinal progeny. Stem Cells   2014;32:1480–1492